Expression of amino acid transporter (LAT1 and 4F2hc) in pulmonary pleomorphic carcinoma - Kaira, Kyoichi; Kawashima, Osamu; Endoh, Hedeki; Imaizumi, Kazuyoshi; Goto, Yasuhiro; Kamiyoshihara, Mitsuhiro; Sugano, Masayuki; Yamamoto, Ryohei; Osaki, Takashi; Tanaka, Shigefumi; Fujita, Atsushi; Imai, Hisao; et al. (Human pathology, 2019)
Amino acid transporters are necessary for tumor growth, metastasis, and survival of various neoplasms; however, the clinicopathological significance of L-type amino acid transporter 1 (LAT1) and 4F2 cell surface antigen (4F2hc) in patients with pulmonary pleomorphic carcinoma (PPC) remainsunknown. The aim of this study is to clarify the prognostic impact of these amino acid transporters in PPC. One hundred five patients with surgically resected PPC were assessed by immunohistochemistry. The expression of LAT1 and 4F2hc, and Ki-67 labeling index were investigated using specimens of the resected tumors. LAT1 and 4F2hc were highly expressed in 35% and 53% of all patients (n = 105, P < .01), 25% and 48% of patients with an adenocarcinoma component (n = 48, P = .02), and 44% and 58% of patients with a nonadenocarcinoma component (n = 57, P = .18), respectively. A high LAT1 expression was significantly related to advanced disease, lymphatic permeation, tumor cell proliferation, and 4F2hc expression. By multivariate analysis, LAT1 and 4F2hc were identified as significant independent markers for predicting a worse prognosis. LAT1 is highly expressed in PPC, and high LAT1 expression can serve as a significant predictor linked to a worse prognosis in patients with PPC. •LAT1 is extensively expressed in patients with pulmonary pleomorphic carcinoma.•LAT1 and 4F2hc are independent prognostic factors for predicting worse outcome.•LAT1 significantly correlates with tumor proliferation, advanced stage, and 4F2hc.